2022
DOI: 10.1038/s41593-022-01176-5
|View full text |Cite
|
Sign up to set email alerts
|

Adult-born dentate granule cells promote hippocampal population sparsity

Abstract: The dentate gyrus (DG) gates neocortical information flow to the hippocampus. Intriguingly, the DG also produces adult-born dentate granule cells (abDGCs) throughout the lifespan, but their contribution to downstream firing dynamics remains unclear. Here, we show that abDGCs promote sparser hippocampal population spiking during mnemonic processing of novel stimuli. By combining triple-(DG-CA3-CA1) ensemble recordings and optogenetic interventions in behaving mice, we show that abDGCs constitute a subset of hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 93 publications
3
43
1
Order By: Relevance
“…We have shown that 3 month-old adult-born neurons are recruited by memory retrieval (Tronel et al, 2015a) and that inhibiting 6 month-old adult-born neurons impairs short-term memory retention, indicating that adult born cells do not need to be young to participate in memory retention (Masachs et al, 2021). Interestingly, 9-12 week-old adult-born neurons lose their ability to promote population sparsity, but become more spatially tuned and can entrain DG principal cells (McHugh et al, 2022), properties that could also support memory accuracy.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…We have shown that 3 month-old adult-born neurons are recruited by memory retrieval (Tronel et al, 2015a) and that inhibiting 6 month-old adult-born neurons impairs short-term memory retention, indicating that adult born cells do not need to be young to participate in memory retention (Masachs et al, 2021). Interestingly, 9-12 week-old adult-born neurons lose their ability to promote population sparsity, but become more spatially tuned and can entrain DG principal cells (McHugh et al, 2022), properties that could also support memory accuracy.…”
Section: Discussionmentioning
confidence: 90%
“…All data shown are mean ± s.e.m. For statistical details, see Table S1 McHugh et al, 2022) which may be related to increased excitability, reduced perisomatic inhibition and enhanced synaptic plasticity (long-term depression and excitation) (Lodge and Bischofberger, 2019;Massa et al, 2011). Recently, it has been shown that neurons aged 4-7-weeks support sparser hippocampal population activity, suggesting that sparse coding may allow for higher dimensional network activity in support of memory accuracy (McHugh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Classical measures of pattern separation, such as orthogonalisation, decorrelation, or spike train distance, are effective at analysing the measured behaviour of a neuronal system and quantify the degree of difference between the inputs and outputs. In the dentate gyrus, outputs are typically encoded by sparser activity than the inputs and sparsity is a major contributor to pattern separation (Rolls and Treves, 1994; Battaglia and Treves, 1998; McHugh et al, 2022). Increasing sparsity in a neural code, however, may reduce the information it carries about the afferent signal (Billings et al, 2014).…”
Section: Resultsmentioning
confidence: 99%